Epidemiological Study on Three Hundred Patients of Scabies in the Industrial Area of Dhaka, Bangladesh - Islam, Kamrul; Zaman, Md. Shah; Kalam, Md. Abul; Islam, Md. Imranul; Siddique, MR; Jahan, Tarana (Journal of Monno Medical College, 2024)
Background: Scabies is a common and highly contagious skin disease caused by a mite called sarcoptes scabiei. Objective: The aim of this study was to analyze the epidemiological factors associated with scabies infection in an industrial area. Methodology: Write the study design, study place, study period and study population here. It was considering age, sex, occupation, economical condition, educational status, family history of scabies of the selected patient. Results: The age group of 1 to 10 years (28.66%) and low socioeconomic condition (58.66%), illiterate (Primary 44.00%), overcrowding living (Madrasah 37.33%) showed the highest infestation rates. Write more findings here Conclusion: In conclusion an improvement of socio-economic conditions, improve living facilities, education, social awareness may contribute to a reduction in the number of scabies infections. Journal of Monno Medical College June, 2024; 10 (1):13-16